'Fossils': A new, fast and open‐source protocol to simulate muscle‐driven biomechanical loading of bone. Issue 3 (3rd January 2023) - Chatar, Narimane; Boman, Romain; Fallon Gaudichon, Valentin; MacLaren, Jamie A.; Fischer, Valentin
Abstract: Finite element analysis (FEA) is a computational method used to predict the behaviour (stresses, strains and deformation) of a structure under predefined loading conditions. It can be applied to different biological structures, such as bone, to study defined muscle‐driven scenarios. However, as muscle is an extremely complex structure to model, evolutionary biologists usually model muscle forces indirectly. In 2007, the BONELOAD MATLAB routine was developed to distribute muscle forces on a surface defined by the user. This routine then had to be coupled with a pre‐existing FEA software (e.g. Strand7) to perform the analyses and has been widely used ever since. In this manuscript, we present a new method to run muscle‐driven finite element simulations on a bone by distributing muscle forces on their insertions area, all within a single environment. We apply this protocol in three different situations: two biting simulations (unilateral and bilateral) and a shoulder flexion simulation. We demonstrate how to prepare the mesh, delineate the muscle origins and insertions, define the constraints, adjust material properties, choose a loading scenario (uniform, tangential or tangential‐plus‐normal), and extract the results. Our automated script meshes the 3D model, defines the constraints and distributes muscle forces within a single simulation software: 'Metafor' (nonlinear solver, owned and distributed by Gesval S.A) or 'Fossils' (a new open‐source linear static solver developed in the frame of this work). 'Metafor' and 'Fossils' can perform the entire protocol (from the meshing to the muscle‐induced simulations) on high‐resolution volumetric meshes (millions of tetrahedra) and rapidly, exceeding the processing time of other widely used software protocols by up to four times. We demonstrate that the results obtained from our protocol are highly congruent with brands such as Strand7. Thus, our protocol opens up the possibility to routinely and rapidly simulate the behaviour of high‐precision muscle‐driven FE models containing millions of tetrahedra. Résumé: L'analyse par éléments finis (FEA) est une méthode de calcul employée pour prédire le comportement mécanique (contraintes et déformations) d'une structure soumise à un chargement donné. Il est possible de l'appliquer à différentes structures biologiques, par exemple, de l'os, afin d'en étudier différents mouvements induits par l'action des muscles. Cependant, les muscles étant des structures extrêmement complexes à modéliser, les biologistes simulent leur action indirectement sur les os. En 2007 le protocole MATLAB du nom de BONELOAD a été développé afin de distribuer une force sur la surface d'insertion musculaire. Ce script a dû ensuite être couplé avec des solveurs préexistants (p. ex. Strand7) pour réaliser les analyses, et a été largement utilisé depuis lors. Dans cette contribution nous présentons une nouvelle méthode permettant de réaliser des simulations par éléments finis pilotées par des forces musculaires en distribuant ces forces sur leurs surfaces d'insertions et le tout dans un environnement de travail unique. Nous appliquons ce protocole dans trois cas de figure: deux simulations de morsures (une unilatérale et une bilatérale) et une rotation de l'épaule. Nous montrons comment préparer les maillages, définir les origines et insertions musculaires, établir les contraintes, définir les propriétés des matériaux, choisir un scénario de chargement (uniforme, tangentiel ou tangentiel‐plus‐normal) et enfin, extraire les résultats. Notre script automatisé crée un maillage, définit les contraintes et applique les forces musculaires le tout dans un seul environnement: « Metafor » (un solveur non linéaire, propriété de Gesval S.A) ou « Fossils » (un nouveau solveur statique linéaire développé dans le cadre de ce travail). « Metafor » et « Fossils » peuvent exécuter le protocole dans son intégralité (du maillage à la simulation de l'action des muscles) sur des maillages volumétriques de très haute résolution (composés de plusieurs millions de tétraèdres) et rapidement, étant jusqu'à quatre fois plus rapide que d'autres solveurs en termes de temps de résolution. Nous montrons également que les résultats obtenus avec notre protocole sont conformes avec ceux obtenus au moyen d'autres solveurs comme Strand7. Ainsi, notre protocole offre la possibilité de réaliser des simulations chargées par des muscles sur des maillages extrêmement précis contenant plusieurs millions de tétraèdres, et ce, de manière rapide et efficace.